(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe clinical characteristics and some undesirable manifestations within the first 24 hours in women undergoing cesarean section under spinal anesthesia at Hai Duong Obstetrics and Gynecology Hospital. Subjects and Methods: A cross-sectional descriptive study was conducted on 174 women undergoing cesarean section under spinal anesthesia at Hai Duong Obstetrics and Gynecology Hospital from November to December 2022. Results: The age group of 25–29 years accounted for the highest proportion (36.8%), with a mean age of 28.98 years. Workers accounted for 59.8% of participants; 39.7% had a previous cesarean section and 36.8% were primiparous. Within the first 24 hours after surgery, 85.1% experienced incision pain, 48.3% uterine contraction pain, and 47.7% physiological shivering. During the uterine safety globe stage, 100% of women had a firm uterus; afterward, 12.6% had a soft uterus. The mean uterine height was 16.66 cm. The amount of lochia was mainly about 200 g (60.3%), and no case exceeded 500 g. Lochia was mainly dark red (67.8%), without blood clots (81.0%), and had a strong fishy odor (98.9%). Recorded undesirable manifestations included delayed flatus (63.8%), nausea and vomiting (47.2%), and headache (24.2%). Conclusion: Within the first 24 hours after cesarean section under spinal anesthesia, common clinical manifestations included incision pain, uterine contraction pain, and physiological shivering. The most frequently recorded undesirable manifestations were delayed flatus, nausea-vomiting, and headache.